A Case Report -Bilateral Giant Achilles Tendon Xanthomas Resection with a Tendon transverse Technique - Al-Shara, Mohamed Baqir (AL-Kindy College Medical Journal, 2019)
Background : Xanthomatosis is a disease in which large tendon tumors can occur, especially in the Achilles tendon. This disease is a rare interesting orthopaedic condition. Case Report:A case of a twenty eight year old girl patient with giant bilateral Achilles tendon xanthomas in which both tumors were resected. There was no ulceration on the both sides. The patient was treated by total resection of the lesion and reconstruction using tendon transfer of the Peroneus brevis and Flexor hallusis longus. Postoperative treatment consisted of six weeks lower leg cast immobilization followed by partial weight bearing. After 4 months the patient was able to walk pain free without any difficulties. It has been suggested that total resection with augmentation had associated with fewer complication of recurrent as compare with a subtotal resection. 10 months after surgery our patient had no signs of recurrence of Achilles tendon swelling. Conclusion: Complete excision of the lesion is needed to reduce recurrence. Reconstruction of the defect is a challenge due to the large defect. Tendon transfer augmentation results in good functional outcome of the patient even in large defects.